Cervical and Anal Human Papillomavirus Infection in Adult Women in American Samoa. (January 2013) - Hernandez, Brenda Y.; Ka'opua, Lana S.; Scanlan, Luana; Ching, John Ah; Kamemoto, Lori E.; Thompson, Pamela J.; Zhu, Xuemei; Shvetsov, Yurii B.; Tofaeono, Jennifer; Williams, Victor Tofaeono
The prevalence of cervical and anal human papillomavirus (HPV) and risk factors associated with infections were evaluated in a cross-sectional study of 211 adult women in American Samoa. Overall, 53% of women reported ever having a Pap smear. Cervical and anal HPV was detected in 10% and 16% of women, respectively; 4% of women had concurrent cervical and anal HPV. The most common cervical genotypes were HPV 6, HPV 16, and HPV 53. Cutaneous HPV types were detected in 40% of anal infections. Cervical HPV infection was associated with anal HPV (age-adjusted odds ratio = 3.32, 1.10-10.00). After age adjustment, cervical HPV was associated with being unmarried, postsecondary education, hot running water at home, multiple sexual partners, nulliparity, condom use, and other contraceptive methods. In multivariate analyses, only age remained associated with cervical HPV and anal HPV. Cervical and anal HPV was more prevalent among younger women; only anal HPV was detected in older women.